ANALISA PROMOSI BRAND AEROSTREET PADA SOSIAL MEDIA INSTAGRAM “LOKAL TAK GENTAR” - Doni Fitri, Nofria; Ghani, Oktaviana; Kusumohendrarto, Raden Hadapiningrani; Yohanda, Derena Martha (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2024)
In this digital era, technology is very helpful in developing several sectors in the economy such as retail (e-commerce), transportation (automated vehicles), education (online courses), health (electronic records), and social interaction (social networks/social media). Apart from helping several sectors in the economy, in this practical digital era it also really helps marketers in promoting their products through social media, for example through Instagram social media. Using Instagram social media is of course very profitable for marketers because Instagram social media doesn't require spending money. to create an Instagram account, and by utilizing social media Instagram can become a gathering place for the target market because Instagram social media has high users and popularity. With the Instagram promotion mix to attract consumer interest in buying the product. Micro, Small and Medium Enterprises (MSMEs) that use Instagram as a promotional medium is a new form of developing and utilizing Instagram in the MSME product sales sector. Instagram is used as a promotional medium because it is more profitable than several other media. One of the MSMEs that uses and utilizes Instagram as a promotional medium is Aerostreet MSMEs located in Dusun 1 Bentangan, Wonosari District, Klaten Regency, Central Java. The purpose of this analysis is to describe the use and utilization of Instagram by Aerostreet MSMEs. This study used descriptive qualitative method. The object of this research is Aerostreet MSMEs which have used Instagram as a promotional media.